Development of an EGFR-targeted Drug Delivery System for Glioblastoma - Zhao, Zi-Ruo (2023)
Glioblastoma (GB) is one of the most malignant cancers with a dismal survival of 4 months when no treatment intervenes. After standard of care: surgery, radiotherapy and temozolomide (TMZ) chemotherapy, its median survival has been increased to 16 months. TMZ functions by methylating guanine of GB DNA into O6-methylguanine, which triggers a futile cycle of base excision-reinsertion conducted by DNA mismatch repair mechanism (MMR), eventually leading to DNA-strands breakdown and cell apoptosis. However, TMZ efficacy is largely limited by factors such as poor in-brain accumulation due to low level permeation across the blood-brain barrier, and O6-methylguanine-DNA methyltransferase (MGMT) which reverses the guanine methylation. The natural transportation protein apoferritin (AFt) shapes as a spherical hollow nanocage and has been proven to be a biocompatible drug delivery vehicle. It possesses 3-4 Å surface channels available for the entrance of iron ions and small molecules and allows modification at its N-termini on the exterior surface with different moieties. The overexpression of epidermal growth factor receptor (EGFR) is often observed in GB and can be seen as a biomarker; while the anti-EGFR affibodies, which are small affinity molecules of strong binding-affinity towards specific target, have been developed for many research purposes, an EGFR-affibody directed AFt delivery system is proposed to promote the performance of TMZ against GB.